The Rise and Decline of U.S. Military Culture Programs, 2004-20 - Mackenzie, Lauren, 1976-; Fosher, Kerry B. (Book collections on Project MUSE., 2021)
"Though the priorities of senior military leaders inevitably change over time, the pressing need for American Service personnel to accommodate the human dimension for success in their ongoing military operations has not diminished. That capability now may be even more important than ever. Almost inevitably, the requirement will reach a critical stage in some future crisis. This book compiles the insights and findings of some of the most determined and resourceful scientists, scholars, and practitioners engaged in the military's culture programs to inculcate the new capabilities in the early twenty-first century. The authors do not gloss over failures and dead ends. Rather, their expectation is that by presenting the bad with the good, they can help future generations engaged in the same task avoid their pitfalls and build on their work. More importantly, the authors hope that their writing might reach those who are still engaged in building cultural capabilities and that they will find encouragement to continue this essential work"--